Understanding Internet Gaming Disorder through the lens of Proactive Coping and Socio-Emotional Well-being among Medical Students - Kumar , Mithlesh; Deurkar, Piyush; Jha, Vikrant; Yaseen, MD; Banjare, Manisha (Journal of Neonatal Surgery, 2025)
Background: Internet usage has increased drastically during the covid-19 pandemic, making the youth most vulnerable to Internet addiction. The possibilities of internet addiction followed by high internet usage, is undoubtedly high. Objective: To explore the social-emotional well-being and proactive coping of medical students with IGD. Methods: This study followed correlational survey research. Through snowball sampling method thirty male medical students were screened for IGD with the help of IGDS9-SF test. A comparative group of healthy medical students screened as non-IGD were also drawn from Delhi medical colleges. Psychological Well Being Scale and Proactive Coping Scale was used to assess socioemotional well-being and proactive coping respectively. Descriptive statistics (mean & SD), inferential statistics (t-test, Pearson correlation & regression analysis) was used to conduct the comparative study. Results: The findings suggest that socio-emotional well-being and that in all its dimensions (satisfaction, efficiency, sociability, mental health and interpersonal relations) and proactive coping of medical students with IGD are significantly low compared to their healthy comparative Non-IGD group. Data showed a significantly positive correlation between proactive coping and socio-emotional well-being and that in all its dimensions. At linear regression socio-emotional well-being and that in all its dimensions were predictive of proactive coping(p<0.001). Conclusion: Socio-emotional well-being and proactive coping of medical students with IGD is significantly low and they are significantly strongly positive correlated and socio-emotional well-being were predictive of proactive coping and needs immediate/timely intervention for their better well-being.